Integration of DBSCAN Cluster Analysis with Multigroup Moderation Path Analysis - Hafizh Syihabuddin Al Jauhar; Solimun Solimun; Rahma Fitriani (CAUCHY: Jurnal Matematika Murni dan Aplikasi, 2025)
This study examines the application of integration between DBSCAN cluster analysis and multigroup moderation path analysis to analyse patterns of waste management behaviour in Batu City. DBSCAN was used to cluster the data based on density, resulting in two main clusters as well as some noise data. The first cluster consisted of 189 respondents, while the second cluster included 196 respondents, with the remaining 10 data identified as noise. The DBSCAN clustering results showed a silhouette index of 0.664, indicating good clustering quality in terms of compactness and separation between clusters. After the data was clustered, each cluster was analysed using multigroup moderation path analysis to assess the relationship between environmental quality, understanding of 3R-based waste management, and economic usefulness of waste with facilities and infrastructure variables as moderators. The results showed that clusters with good quality facilities had a stronger understanding of 3R-based waste management and its economic usefulness. This finding underscores the importance of facilities and infrastructure in influencing community waste management behaviour patterns.